2019
DOI: 10.20473/cdj.v8i1.2018.42-48
|View full text |Cite
|
Sign up to set email alerts
|

PERBEDAAN KHASIAT ANTIBAKTERI BAHAN IRIGASI LARUTAN PROPOLIS DAN SODIUM HYPOCHLORITE TERHADAP BAKTERI Streptococcus viridans

Abstract: Background. Bacteria is main etiologycal factor of pulpo-periapical disease. Therefore, eliminating bacteria is the important part on root canal treatment. It can be obtained by using irrigation agent that has antibacterial effect and endodontic sterilization agent. Beside of its antibacterial effect, the ideal irrigation agent should has an ability to remove necrotic tissue and less toxic. Propolis is well known as a natural substain that has antibacterial effect and less toxicity. So, it has a potential use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
2
0
2
Order By: Relevance
“…19 In contrast to 2.5% NaOCl which only consists of a few chemical elements such as sodium, oxide, and chlorine has a complex antibacterial mechanism through saponification, neutralization and chloramination reactions so that is more effective at inhibiting bacterial growth. 20 Based on the research, it can be concluded that 6.25% and 12.5% green okra extract has inhibition against E. faecalis. 12.5% green okra extract is a concentration with an inhibitory strength close to 2.5% NaOCl, but there is no concentration of green extract that effectively inhibits E.faecalis equivalent to 2.5% NaOCl.…”
Section: Discussionmentioning
confidence: 95%
“…19 In contrast to 2.5% NaOCl which only consists of a few chemical elements such as sodium, oxide, and chlorine has a complex antibacterial mechanism through saponification, neutralization and chloramination reactions so that is more effective at inhibiting bacterial growth. 20 Based on the research, it can be concluded that 6.25% and 12.5% green okra extract has inhibition against E. faecalis. 12.5% green okra extract is a concentration with an inhibitory strength close to 2.5% NaOCl, but there is no concentration of green extract that effectively inhibits E.faecalis equivalent to 2.5% NaOCl.…”
Section: Discussionmentioning
confidence: 95%
“…NaOCl hanya terdiri dari sedikit unsur kimia, yaitu natrium, oksida dan klorin sehingga memiliki daya antibakteri yang maksimal. 21 Ekstrak kasar BOH yang menggunakan pelarut organik (etanol) dalam proses ekstraksi seringkali mengandung senyawa yang tidak diinginkan seperti zat warna (klorofil a dan b, karotenoid, antosianin), karbohidrat, lilin, resin. 22 Keberadaan semua senyawa tersebut menyebabkan ketidakstabilan sifat fisika ekstrak ketika akan diformulasikan serta dapat mengurangi kadar senyawa aktif dalam ekstrak.…”
Section: Pembahasanunclassified
“…Larutan irigasi yang umum digunakan dalam endodontik, yaitu CHX 2%, karena memiliki efek antimikoba yang luas dan dapat bertahan lama dengan kemampuannya melekat pada dinding saluran akar. [6][7][8] Pemanfaatan bahan alam sebagai obat tradisional di Indonesia akhir-akhir ini meningkat, bahkan beberapa bahan alam telah diproduksi secara fabrikasi dalam skala besar. Penggunaan obat tradisional dinilai memiliki efek samping lebih kecil dibandingkan dengan obat dari bahan kimia, selain harganya lebih terjangkau.…”
Section: Pendahuluanunclassified